Antidepressant and anxiolytic potential of Citrus reticulata Blanco essential oil: a network pharmacology and animal model study - Khanh Nguyen, Nhi Phuc; Kwon, Ji-Hye; Kim, Min-Kyung; Tran, Khoa Nguyen; Huong Nguyen, Ly Thi; Yang, In-Jun (Frontiers in Pharmacology, 2024)
Background: Citrus reticulata Blanco essential oil (CBEO) has attracted increasing attention as a potential treatment for depression and anxiety in recent years. However, there is limited evidence regarding the active compounds responsible for its therapeutic effects. In addition, substantial amounts of CBEO and prolonged therapy are often required. This study aims to investigate the rapid acting antidepressant and anxiolytic effects of CBEO, identify the underlying composition as well as optimize its dosage and duration. Methods: CBEO composition was determined using gas chromatography–mass spectrometry (GC–MS), and the corresponding targets were obtained from the SwissTargetPrediction database. Depression-related targets were collected from DisGeNET, GeneCards, Therapeutic Target Database, and Online Mendelian Inheritance in Man. Subsequently, the overlap between CBEO and depression targets was utilized to build a network diagram depicting the relationship between the active ingredients and targets using Cytoscape software. The STRING database facilitated the construction of a protein–protein interaction network, and the Ma’ayan Laboratory Enrichment tool was employed for Gene Ontology (GO) enrichment, Kyoto Encyclopedia of Genes and Genomes (KEGG), and Wiki pathway analyses. Molecular docking was conducted using AutoDock Vina and Discovery Studio Visualizer. Topological analysis predicted the main antidepressant active ingredients in CBEO. A mixture of these compounds was prepared based on their relative GC–MS ratios. Tail suspension test, elevated plus maze, corticosterone-induced PC12 cells, and lipopolysaccharide (LPS)-induced BV2 cells were used to validate the antidepressant and anxiolytic potential of CBEO and CBEO’s main bioactive constituents. Results: CBEO contains 18 components that target 121 proteins. We identified 595 targets associated with depression; among them, 29 targets were located between essential oils and depression. Topological results revealed that linalool, p-cymene, α-terpinene, terpinen-4-ol, and α-terpineol were the major active compounds of CBEO in the management of depression. GO analysis identified G protein-coupled opioid receptor activity, phospholipase C-activating G protein-coupled receptor, and neuron projections that were mostly related to molecular functions, cellular components, and biological processes. Neuroactive ligand-receptor interactions, chemical carcinogenesis, and calcium signaling pathways were the major pathways identified in KEGG analysis. Molecular docking showed that the main bioactive ingredients of CBEO had favorable binding affinities for Protein-Protein Interaction’s hub proteins, including OPRM1, PTGS2, ESR1, SLC6A4, DRD2, and NR3C1. These five compounds were then mixed at 0.8:5:0.6:2:1 (w/w) ratio to form a CBEO antidepressant active compound mixture. An acute intranasal treatment of CBEO (25 mg/kg) only demonstrated an antidepressant effect, whereas the main bioactive compounds combination (12.5 mg/kg) illustrated both antidepressant and anxiolytic effects in mice. Linalool, p-cymene, and terpinene-4-ol exhibited neuroprotective and anti-neuroinflammation in the in vitro study, while these effects were not observed for α-terpinene and α-terpineol. Conclusion: Linalool, p-cymene, α-terpinene, terpinen-4-ol, and α-terpineol cymene might be mainly contributing to CBEO’s antidepressant effect by regulating neuroactive ligand-receptor interaction, neuron projection, and receptor signaling pathway. A mixture of these compounds showed rapid antidepressant potential via intranasal administration, which was comparable to that of CBEO. The mixture also exhibited an anxiolytic effect while not seen in CBEO.